Analysis Of Lift In A Hovercraft Numerical Simulation - Ho, Teik Seng (Universiti Sains Malaysia, 2005)
This final year project report, entitle: ‘Analysis of lift in a hovercraft (numerical simulation)’, is done by Ho Teik Seng under the supervision of University Sains Malaysia Mechanical School lecturer, Prof. K.N.Seetharamu and guidance from Mechanical School master student 2004/05, Mr Lee Heng Hwa. The analysis is done by using HoverANALYSIS program, which had been written by Mr. Phoon Lam Cheng with the help of MATLAB software. This program is a Finite Element Method based program which compatible to analyze the pressure distribution, load capacity, volumetric flowrate and power required of a hovercraft under certain circumstances. The objectives of this project are to determine the minimum power required for a given lift and the maximum lift for a given power. The specific hovering height, air pressure, number of nodes, number of elements, and other parameters of the hovercraft had been set and analysis carried out to obtain the load capacity, volumetric flowrate and power required for each condition. The effect of number of slots, the way of supply slots placement, distance between supply slots and slot size on to the load capacity, volumetric flowrate and power required have been studied and analyzed. Based on the analysis, the number of supply slots in the hovercraft should be increased in order to obtain minimum power required. However, only 2 supply slots should be installed into the hovercraft with 800mm distance between the supply slots in order to optimize the hovercraft lift.